Using Q-Learning for Recommend Learning Object on e-Learning System - Hasibuan S Muhammad (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
This paper discusses the software development used for theselection of instructional materials based on an appropriatelearning style. Q-Learning is used to estimate state-actionlearners using Q-Learning. It is conducted by calculating thevalue of the action done to reward students in selectingteaching materials, so the pattern matches are found. Thisstudy uses the Felder Silverman Learning Style Model(FSLSM). Tests showed that the system is able to perform theselection (action) of instructional materials for teachingmaterials that match learning styles. Q-Learning Lessons canbe applied to optimize the selection of instructional materialswith minimal effort